Methodologies to Measure the Gender Dimensions of Crime and Violence - Shrader, Elizabeth (World Bank, Washington, DC, 2014)
Recent studies have used homicide rates, police statistics, and crime victimization surveys to pinpoint violent areas. The author argues that these useful measures of crime, and violence underestimate certain types of violence (especially non-economic violence) and key dimensions of violence (especially age, and gender). A composite index based on monitoring, and surveillance of homicides, crime statistics, and victimization surveys can provide invaluable "first round" snapshots of urban violence - information to monitor crime trends, warn against incipient crime waves, and indicate areas where more in-depth "second round" studies are needed to explore casualty, the impact of interventions, and public opinion. But a composite index of municipally generated information about trends, depends heavily on the quality of the data collected, and will not explain why trends, or changes occur. Other indicators are needed to strengthen surveillance, and to facilitate the planning of interventions, and evaluation. It would be helpful, for example, to distinguish between social, economic, and political violence, and to provide items on autopsy reports, crime statistics, and victimization surveys to gain insight into what motivates violence. Information useful for analyzing causes of violence might include: 1) Individual: socioeconomic data about victims, and perpetrators, and information about their use of alcohol, drugs, or firearms. 2) Interpersonal: whether victim, and perpetrator belonged to the same family, or household, had an affective relationship, were acquaintances, or were strangers. 3) Institutional: crime characteristics (physical injuries sustained, weapons used, value of property lost, where crime occurred); characteristics of victim, and perpetrator; whether the crime was reported; per capita police, and private security; presence of gangs in community; estimated number of gangs and gang members; level of gang organization (low, medium, high); and, other measures of social capital. 4) Structural: levels of impunity (number of convictions as a ratio of number of arrests); levels of corruption; indices of social exclusion, such as racism, gender discrimination, or areas stigma; the dynamics between violence, and access to (and control of) such resources as land, water, and wealth. Crime mapping, to provide visual confirmation of noted trends, might be combined with information about the relative locations of battered women's shelters, police stations, and the distribution of family violence in residential areas.